2020
DOI: 10.1007/s42452-020-03794-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sintering temperature and particle size on permeability of functionally gradient composite porous materials prepared by hanging slurry process

Abstract: Porous materials have excellent functions in filtration and purification, and gradient composite porous materials enrich the product types of porous materials in the same field. In the preparation of metal-ceramic gradient composite porous materials, the matching relationship between the pore morphology and pore size of the metal porous matrix and the coated powder particles will seriously affect the structure and performance of the ceramic membrane. This work mentions the different size range (60, 100, 200 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The powder particle size and the distribution affected the viscosity of the ceramic suspension, the movement of the particles in ceramic suspension during phase inversion, and the particle migration and bindings during sintering at high temperatures (Konijn et al 2014;Renteria et al 2019;Li et al 2020a). Moreover, powder particle size and the distribution of the starting material (raw material) affected the morphology characteristic and the porosity of the fabricated ceramic membrane (Hubadillah et al 2016a(Hubadillah et al , 2021Ji et al 2020).…”
Section: Characterization Of Starting Materials and Membranesmentioning
confidence: 99%
“…The powder particle size and the distribution affected the viscosity of the ceramic suspension, the movement of the particles in ceramic suspension during phase inversion, and the particle migration and bindings during sintering at high temperatures (Konijn et al 2014;Renteria et al 2019;Li et al 2020a). Moreover, powder particle size and the distribution of the starting material (raw material) affected the morphology characteristic and the porosity of the fabricated ceramic membrane (Hubadillah et al 2016a(Hubadillah et al , 2021Ji et al 2020).…”
Section: Characterization Of Starting Materials and Membranesmentioning
confidence: 99%
“…At present, the filtration of porous metal materials in harsh environments has received much attention, but there are still some problems such as low filtration accuracy and small permeability. Studies have shown that gradient porous materials can effectively improve filtration accuracy on the basis of maintaining a good permeability (Ji et al, 2020). Therefore, the research and application of gradient porous materials are now the focus of research.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing sintering temperature, the permeability of porous materials usually decreases, and pore size rarely changes or slightly decreases [ 21 , 22 ]. However, early studies have shown that the permeability and pore size of porous materials both increase with sintering temperature [ 23 , 24 , 25 , 26 , 27 ]. Some of these results are attributed to the liquid phase during sintering [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%